PERAN SISTEM INFORMASI AKUNTANSI DALAM PENYALURAN KREDIT PADA PERUSAHAAN JASA PERBANKAN - Bq. Anggun Hilendri; Sapto Hendri B. S. (Jurnal Aplikasi Akuntansi, 2019)
Banks are one of institution, where the main activities are in the financial sector. One of the financial activities carried out by banks is in granting credit. The existence of Mataram BTN Bank has a very important role in encouraging development and increasing economic growth in Mataram. However, the problem in lending is how to minimize the risk of bad credit. With the existence of the role of an adequate accounting information system in the process of granting credit shows an attitude of caution in the banking itself. This research will focus on lending with house collateral at the Mataram BTN bank. This type of research is descriptive. Respondents in this study were Supporting Deputy Branch Managers and accounting control units. The results of the study show that the credit giving accounting information system applied at Mataram BTN bank is effective and can support the internal control system. The practical implications of this research are expected to provide a view to other banking service companies that the accounting information system in lending is very important. With the existence of an effective accounting information system will produce information that is in accordance with needs, accurate, functioning and can be trusted.